Desenvolvimento de nova técnica de interrogação e análise analítica aplicadas a sensores interferométricos em fibra - Scandian, Lorenzo Bortolon (2019)
The use of sensitive devices is of great importance from industrial applications, such as in fuel storage systems, biochemical processing, and even in medicine. Most of the sensors currently in operation have traditional operability principles, being based on mechanical and electrical techniques. As a result, their applicabilities are restricted when used in some type of environment. In addition, often their manufacturing costs may not be accessible due to the complexities required in their constructions and their sensitivities and resolutions may not be as great as needed. The need for a sensor without the aforementioned restrictions boosted research in the area of optical sensing so that the use of optical fiber for measurements has been used for some years. Many limitations, costs and risks are considerably reduced with this technology. Among the wide range of available optical sensors, those who use interferometric interrogations often excel in this area because of their superior sensitivities and satisfactorily stable measurements. They also offer a variety of spectrum analysis techniques. However, one of the limitations of this type of sensor is related to its length. In general, fiber sensors commonly lack the ability to perform distributed measurements of liquid levels, for example, to lengths of a few tens of centimeters, accurately. This dissertation proposes to investigate the viability of a liquid level sensor based on interferometric phenomena in optical fiber for measurements greater than 120 mm using a spectral analysis based on the use of the amplitude of the spectrum curves originated to the detriment of the interference phenomena. The main aspect to be addressed is the investigation of the feasibility of using the information of the variation of the amplitudes of these curves, already provided by the prospecting of existing interferometric sensors, as useful content to be analyzed in order to assert a valid relation between this variation of amplitude and the change of liquid level in a given container, characterizing the construction of a sensor. It is also part of the scope of this dissertation to demonstrate how a simple analytic computational model using plane waves can, in this specific case, result in reliable predictions of measurements for sensors of different lengths.